Too little, too late? Rice production to mitigate climate change in Colombia - Generale, Giovanni; Ibarra Medina, Lina Marcela; Romero Sánchez, Miguel Antonio; González, Carolina; Andrade, Robert Santiago (2022)
Climate change has proven to threaten agriculture and food security given the close relationship between agricultural outcomes and climate conditions (e.g., rainfall, temperature, radiation). Consequently, and recognizing that production management practices exacerbate the problems and are responsible for low crop performance we are interested to evaluate if efforts to achieve climate-resilient and sustainable production have generated an impact. In this presentation, we focused on rice production in Colombia and evaluate how climate change effects on rice can be mitigated by adopting certain practices and technologies recommended and developed by FEDEARROZ. We use Propensity-match-score methods and find that those farmers adopting improved management recommendations show higher yields and less Greenhouse Gas Emissions due the management practices disseminated by FEDEARROZ. This result remark the importance to continue investing in rice research while also concentrating efforts to improve scaling-up.